Patient Engagement in Health Management as a Mediator Between Perceived Risk and COVID-19 Related Distress in Patients With IBD: A Structural Equation Model - Castellini, Greta; Palamenghi, Lorenzo; Savarese, Mariarosaria; Barello, Serena; Leone, Salvatore; Previtali, Enrica; Armuzzi, Alessandro; Graffigna, Guendalina (Frontiers in Psychiatry, 2021)
Objective: This study aimed to evaluate the impact of the COVID-19 emergency on patients with IBD’s psychological distress, understanding the role of patient engagement as a mediator. Methods: An online questionnaire was created, measuring: perceived risk susceptibility towards COVID-19, perceived stress, patient engagement. The questionnaire was distributed to a purposive sample of IBD patients who belonged to the Italian Association for patients with IBD (AMICI Onlus) in April 2020. Structural equation models were implemented. Results: the effect of the perceived risk susceptibility towards COVID-19 contagion on the perceived stress is fully mediated by the patient engagement (β= 0.306, p-value < .001). Moreover, the Patient Engagement mitigates the perceived stress (β = -0.748, p-value < .001) in our sample of IBD patients, and it is negatively influenced by the Perceived Risk susceptibility towards COVID-19 (β = -0.410, p-value < .001). Conclusions: patient engagement is the key factor to reduce the perceived psychological distress during this COVID-19 emergency and to protect the patients with IBD from a worsening of their disease.